The socio-political scene and Henry’s crisis influence on the curricula of physical education undergraduate courses in Brazil - Alexandre Janotta Drigo; Luiz Henrique da Silva; Heidi Jancer Ferreira; Cláudio Silveiro da Silva; Samuel de Souza Neto (Revista da Educação Física)
From 1980s to 1990s, the Brazilian Physical Education (BPE) was strongly influenced by the discussion concerning its identity as an academic discipline; the final period of the Brazilian military dictatorship; the regulation of the BPE as a profession. Hence, this study analyzed the influence of that epistemological and political setting on the curricula of three BPE undergraduate courses. The Political Pedagogic Project and the Curriculum Matrix of the three undergraduate courses, from public universities, were analyzed using two qualitative research techniques: body of knowledge analysis, and content analysis. The results showed that the curricula analyzed did not cover a definition of professional intervention procedures based on ethical conduct specific to the area. Furthermore, the knowledge basis of the curricula is mainly constituted by discipline knowledge, which contributes to distancing the student’s training from their field of professional practice . These findings may be associated with the insufficient epistemological discussion early  initiated by Henry’s works and unclear definition if the BPE is an academic or professional area. This investigation suggests that political disputes related to professionalization of BPE overlapped the academic discussions, which might have contributed to the problems identified on the preparation through bachelor courses of physical education professionals.